2018
DOI: 10.1134/s1063776118110171
|View full text |Cite
|
Sign up to set email alerts
|

Concepts for a Deuterium–Deuterium Fusion Reactor

Abstract: We revisit the assumption that reactors based on deuterium-deuterium (D-D) fusion processes have to be necessarily developed after the successful completion of experiments and demonstrations for deuterium-tritium (D-T) fusion reactors. Two possible mechanisms for enhancing the reactivity are discussed. Hard tails in the energy distribution of the nuclei, through the so-called κ-distribution, allow to boost the number of energetic nuclei available for fusion reactions. At higher temperatures than usually consid… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Unlike PP cycle, CNO cycle starts heavier element 12 C which produced by triple alpha process which three alpha particles are fused into carbon 4 He + 4 He → 8 Be , 8 Be + 4 He → 12 C * + 2γ…”
Section: Stellar Fusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike PP cycle, CNO cycle starts heavier element 12 C which produced by triple alpha process which three alpha particles are fused into carbon 4 He + 4 He → 8 Be , 8 Be + 4 He → 12 C * + 2γ…”
Section: Stellar Fusionmentioning
confidence: 99%
“…⟨𝛔𝒗⟩ is reactivity and 𝑻 is temperature [4].In Figure1, D T fusion has much higher cross section which means the possibility of reaction is higher than D D fusion over same temperature. With κ distribution, D T fusion at relatively low temperature, the reactivity gains of two orders of magnitude compare with the Boltzmann energy distributions[4]. In fact, κ distribution provide a straightforward replacement of the Maxwell distribution for systems out of the thermal equilibrium such as space plasmas[5].…”
mentioning
confidence: 99%
“…In 2006, Nakamura et al [11] confirmed that non-Maxwellian knock-on perturbations caused by close collisions between alpha particles and background ions would result in reactivity enhancement in fusion reactions. Subsequently, studies on the effect of reactant distributions with high-energy tails in fusion reactions, such as the kappa distribution [17][18][19], have been conducted. Overall, these findings suggest that non-Maxwellian distributions have a significant impact on fusion reactivity and open up new avenues for enhancing fusion efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Among the various assumptions in these models, the fact that colliding particles may not share energies according to a Maxwell-Boltzmann (MB) probability distribution, as far as we know, has never been systematically scrutinized in the context of plasma fusion, apart from the possible impact in terms of nuclear fusion reactivities (Onofrio 2018). This is at variance with the astrophysical plasmas for which deviations from MB have been discussed (Nicholls, Dopita & Sutherland 2012;Nicholls et al 2013;Storey & Sochi 2014Draine & Kreisch 2018).…”
Section: Introductionmentioning
confidence: 99%